An Economic Assessment of Low-Carbon Investment Flows in the U.S. Power Sector - Lu Wang; Alice Favero; Marilyn Brown (Fondazione Eni Enrico Mattei (FEEM), 2016)
This study used the GT NEMS model to analyze how the proposed federal regulation on carbon emissions will impact investments in the U.S. electricity generating capacity at the federal and Census Division level for 2016-2030. Results show that in order to reduce emissions by 32% by 2030, cumulative investments will increase from 399 to 414 billion USD by 2030. Under the scenario which addresses carbon leakage - covering new and existing power plants - cumulative investment will reach 475 billion USD by 2030. Addressing carbon leakage will affect not only the size of the investments but also the direction: when only existing power plants are covered investments in natural gas remains almost unchanged (123 billion USD) relative to the Reference case; while under the scenario that covers all power plants, investment in natural gas will be 24% lower and the investments in renewable will be 64% higher than the Reference. Carbon regulation will produce not only losers and winners among energy sources but also among U.S. states. While the South and Midwest states will experience much higher increase in cumulative investments with respect to the national average; Northeast and West states will reduce their overall investments by 2030 under the policy scenarios.
Keywords: Q42; Q43; Q48; Q58; 330; Clean Power Plan; Climate Change Mitigation Policy; Investment; Electricity; United States